Effect of Various Disinfectants on E. coli Isolated from Water Pipes in Broiler Farms at Giza and Dakahlia Governorates, Egypt - Abd El-Razek, Nouran; Hassan , Heba; Abd El-Tawab, Ashraf (Journal of Advanced Veterinary Research, 2023)
In poultry, Escherichia coli infections lead to substantial deaths and financial losses for producers each year. This study aimed to investigate the prevalence of E. coli from water pipes and drinkers in broiler farms, to characterize the isolated E. coli strains in terms of serotypes, biofilm production degree, presence of the adrA gene. The gene "adrA" encodes for the adhesion regulating protein A. adrA is a protein that plays a role in regulating the adhesion and biofilm formation of E. coli bacteria., and the efficacy of various disinfectants on E. coli biofilms. A total of 100 swab samples were collected from drinking water pipes and drinkers from different broiler farms in Giza and Dakahlia governorates in Egypt. Out of them, 18 E. coli serogroups were identified in 50 positive samples, and the most predominant serogroup was O91, which showed the highest incidence (20%), followed by serotypes O78 (18%), and O26 (8%). Microtiter-plate test for determination of biofilm production for 50 E. coli isolates were performed. PCR was done for the detection of the virulence gene adrA in the 13 strong biofilm E. coli isolates, and the results revealed that 100% were positive for the virulence gene. The effect of disinfectants on E. coli was studied by using ZnO nanoparticles, acidifiers, and quaternary ammonium dioxide. This study found a high prevalence of E. coli in water samples, identified various E. coli serotypes, observed biofilm production, and determined the effectiveness of different disinfectants on E. coli isolates.